1985
DOI: 10.1063/1.449518
|View full text |Cite
|
Sign up to set email alerts
|

Electron spin resonance line shapes of randomly oriented molecules in septet and nonet states by a perturbation approach

Abstract: The electron spin resonance line shapes of randomly oriented molecules in septet and nonet states are analyzed in terms of the formulas derived from a perturbation treatment to third-order in the fine-structure energy. The method is applied to a ground-state septet hydrocarbon, 3, 3'diphenylmethylenebis (phenylmethylene), and a ground-state nonet hydrocarbon, mphenylenebis[(diphenylmethylen-3-yl)methylene], randomly oriented in mixed polycrystalline powders of benzophenone. It is shown that the g factor and th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
22
0

Year Published

1988
1988
2013
2013

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 68 publications
(26 citation statements)
references
References 23 publications
4
22
0
Order By: Relevance
“…11 and 12 are investigated here, are well established on experimental grounds. [17][18][19][20][21][22][23][24][25][26][27][28] Similarly, Schlenk hydrocarbon biradicals with m-phenylene bridged biradicals have the triplet ground states, 64 supporting the computational results for 2. On the other hand, DFT results indicate that the stabilities of highspin states are lower for charged molecules 4 and 5 than for neutral molecules 1-3.…”
Section: A Relations To Recent Experimentsmentioning
confidence: 62%
See 1 more Smart Citation
“…11 and 12 are investigated here, are well established on experimental grounds. [17][18][19][20][21][22][23][24][25][26][27][28] Similarly, Schlenk hydrocarbon biradicals with m-phenylene bridged biradicals have the triplet ground states, 64 supporting the computational results for 2. On the other hand, DFT results indicate that the stabilities of highspin states are lower for charged molecules 4 and 5 than for neutral molecules 1-3.…”
Section: A Relations To Recent Experimentsmentioning
confidence: 62%
“…From experimental [17][18][19][20][21][22][23][24][25][26][27][28] and theoretical 11,13,14,[29][30][31] studies of magnetic interactions, well-known organic magnetic molecules with the ferro͑antiferro͒magnetic ground state are m-͑p-or o-͒ phenylene-bridged organic polyradicals. The meta-isomers have usually more stable high-spin states with a parallel spin configuration than low-spin states with an antiparallel spin configuration between radical sites.…”
Section: Introductionmentioning
confidence: 99%
“…Figure 1 shows the simulated spectrum of the quartet photoexcited state of the p-radical 1 [8b] (the inset of Figure 1) as well as the one observed at 800 ns after laser excitation. X, Y, and Z are assigned to the X, Y, and Z principal-axis canonical transitions and A is an off-axis extra line [17,26] (n = 9.0935 GHz, 2B 1 = 0.012 mT and T = 30 K). The spin Hamiltonian parameters used in this simulation are g = 2.0043, D = 0.0225 cm À1 and E = 0.0 cm À1 .…”
mentioning
confidence: 99%
“…with g = 2.002, D = +0.03161 and E = -0.00394 em-', and S = 4, confirming the tetracarbene to be in the nonet state. Temperature dependence of the total signal intensity in the range 1.8-56 K showed that the observed nonet state is the ground state, while the other states are located at least 300 cm-I above the ground state [9]. The effective exchange energy between the carbenic centers are estimated by a theoretical study based on the periodic Kondo-Hubbard model to be ca.…”
Section: First High-spin Organic Moleculesmentioning
confidence: 95%